(untitled) (ModaPalavra e-periódico, 2025)
This article aims to diagnose, through a Design Management approach, a Professional and Career Guidance project aimed at the Fashion area, offered at a public educational institution. To this end, applied research was carried out, with a qualitative approach and exploratory and descriptive objectives, divided into two phases: Theoretical Foundation and Case Study. In the Case Study, the Guidance Guide for Project Development - GODP (Merino, 2016) was used, a methodology organized in a sequence of actions that allow conscious planning of Design, considering the largest possible number of elements that meet the objectives of a product or service project. As a result, the diagnosis made it possible to identify the potentialities and weaknesses of the extension project, enabling the proposition of actions aimed at its reformulation, especially regarding inclusion in the institutional calendar, in-person execution, and preparation of support materials for organizing the information collected by participants throughout the Orientation process, among other aspects.